Delayed gastropericardial fistula following gastric pull-up - Sunita Ojha; Rajesh Bhojwani; Prabhar Srivastava; Goutam Sen (Journal of Pediatric Surgery Case Reports, 2021)
Gastro-pericardial fistula (GPF) is a rare condition, caused by trauma, benign or malignant pathology. Rare case of delayed complication of retrosternal gastric conduit for esophageal atresia presenting 18 years after surgery as GPF is discussed. Thoracoscopic excision of GPF was done. Treatment strategies for GPF require drainage of pericardium, fistula resection, defunctioning esophagostomy/gastrostomy. Thoracoscopy is better modality to manage such cases avoiding morbidity of sternotomy in moribund patient. While operating pediatric patients for gastric conduit advantage of reduced incidence of GPF in posterior mediastinal placement should be considered, because GPF might manifest as late as 18–20years.